Metal-organic framework derived Fe-Co-CN/reduced graphene oxide for efficient HER and OER. (1st January 2021) - Fang, Wenhui; Wang, Jing; Hu, Ye; Cui, Xiaoqing; Zhu, Ruifeng; Zhang, Yuhua; Yue, Chaochao; Dang, Jiaqi; Cui, Wei; Zhao, Hong; Li, Zengxi
Highlights: A novel hybrid electrocatalyst Fe-Co-CN/rGO-700 was synthesized with a simple and effective way. The synergistic effect of Fe-CN and Co-CN makes an excellent electrocatalytic performance of Fe-Co-CN/rGO-700 towards HER and OER. The proposed catalyst Fe-Co-CN/rGO-700 has an outstanding durability. Abstract: It's a major challenge to explore highly active and stable electrocatalysts for efficient hydrogen evolution reactions (HER) and oxygen evolution reactions (OER). In this work, we report a new hybrid electrocatalyst: iron-cobalt decorated nitrogen doped carbon/reduced graphene oxide-700 °C (Fe-Co-CN/rGO-700). The catalyst shows an excellent electrocatalytic performance toward HER and OER in alkaline solution, which has lower overpotentials of 0.215 V and 0.308 V at the current density 10 mA cm −2, respectively, and this catalyst has an outstanding durability (after 45 h). The excellent activity mainly benefit from the highly dispersed iron/cobalt species, sheet structure with high porosity, the improvement of electronic structures with nitrogen-doped carbon and high conductivity of rGO. Combined with the density function theory (DFT) calculations, the improvement of the HER and OER performance were also attributed to the balance of adsorption/desorption of the hydrogen and oxygen-containing intermediates, and the increased electronic states density near the Fermi level. The proposed work provides a novel and simple strategy to synthesize a porous carbon electrocatalyst material using metal-organic frameworks (MOFs) as precursor with high activity and strong stability for HER and OER. Graphical abstract: Image, graphical abstract